Effects of reinforcement choice on task responding in individuals with developmental disabilities. - Lerman, D C (1997)
The effects of reinforcement choice on task performance were examined with 6 individuals who had been diagnosed with severe to profound mental retardation. Five highly preferred items were identified for each participant via stimulus preference assessments. Participants then were exposed to choice and no-choice conditions that were alternated within reversal and multielement designs. During choice sessions, participants were permitted to select between two preferred stimuli contingent on responding. During no-choice sessions, the therapist delivered a single item contingent on responding. Preference for the stimuli was held constant across conditions by yoking the items delivered during no-choice sessions to those selected during the immediately preceding choice sessions. All participants exhibited similar rates of responding across choice and no-choice conditions. These findings indicate that for individuals with severe disabilities, access to choice may not improve task performance when highly preferred items are already incorporated into instructional programs.